Variation in Bird Eggs—Does Female Factor, Season, and Laying Order Impact the Egg Size, Pigmentation, and Eggshell Thickness of the Eggs of Capercaillie? - Joanna Rosenbeger; Kamil Pytlak; Ewa Łukaszewicz; Artur Kowalczyk (Animals, 2021)
Despite numerous studies, intra-species variation in bird eggs is still not well explained. In the presented studies, we investigated the possible sources of this variation: female factor, laying order, and season, using the following traits of Capercaillie eggs as an example: egg size and shape, eggshell lightness, and thickness. Samples were collected for three years from three Capercaillie breeding centres located in different parts of Poland, where birds are kept in conditions close to their natural habitat and have a similar diet. The obtained results showed no significant impact of laying order on egg size, shape, pigmentation, nor eggshell thickness. This indicates that the provided nutrition ensures an adequate supply of minerals for the entire laying period. Most results did not show statistically significant differences between eggs from different breeding centres, but in one breeding centre, eggshells had lighter pigmentation. We assume the observed differences may result from females’ individual features or local environmental conditions. Egg traits were highly consistent for individual females, proving that visual identification can be useful in identifying the eggs of different females.